(2, 6-Dichloro-4-iodophenyl)bis(2, 4, 6-trichlorophenyl)methane as a precursor in efficient cross-coupling reactions for donor and acceptor functionalized triphenylmethyl radicals. (December 2022) - Arnold, Mona E.; Kuehne, Alexander J.C.
Abstract: To date, the functionalization of the tris(2, 4, 6-trichlorophenyl)methyl radical (TTM) is restricted to strong electron donating groups, whereas other substituents give only low or no reaction yields. Here, we present the synthesis of a mono-iodized derivative of the protonated TTM precursor (HTTM). It reacts readily in various types of cross-coupling reactions to give access to triphenylmethyl radicals functionalized with the respective electron donating or electron accepting groups. Iodized HTTM overcomes current limitations in accessibility and yield for TTM radicals functionalized with weaker electron donating groups and electron accepting groups, enabling the synthesis of virtually any desired TTM radical derivative. The performance of iodized HTTM is demonstrated by the synthesis of new stable radical compounds that are otherwise not or hardly accessible. Trimethoxyphenyl is introduced as a first nitrogen-free substituent of electron donating strength comparable to carbazole or diphenylamine. As electron accepting groups, we employ motifs such as benzophenone and pyrimidine and study the respective radicals for their optical properties.